2017
DOI: 10.48550/arxiv.1701.08696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urban Attractors: Discovering Patterns in Regions of Attraction in Cities

Abstract: Understanding the dynamics by which urban areas attract visitors is significant for urban development in cities. In addition, identifying services that relate to highly attractive districts is useful to make policies regarding the placement of such places. Thus, we present a framework for classifying districts in cities by their attractiveness to visitors, and relating Points of Interests (POIs) types to districts' attraction patterns. We used Origin-Destination matrices (ODs) mined from cell phone data that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…This study additionally identified attraction patterns by analyzing visitor numbers, visitor distance distribution, and visitor origin spatial dispersion. Nevertheless, the aforementioned methodology may introduce imprecision when attempting to identify urban attractions due to the restricted capability of identifying sites of interest in situations involving traffic congestion caused by visitors traversing the street network [19]. In addition, specific attractiveness factors have not yet been identified in this research.…”
Section: Research Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…This study additionally identified attraction patterns by analyzing visitor numbers, visitor distance distribution, and visitor origin spatial dispersion. Nevertheless, the aforementioned methodology may introduce imprecision when attempting to identify urban attractions due to the restricted capability of identifying sites of interest in situations involving traffic congestion caused by visitors traversing the street network [19]. In addition, specific attractiveness factors have not yet been identified in this research.…”
Section: Research Statusmentioning
confidence: 99%
“…A study examining the appeal of a city through the lens of tourism or staycations was conducted. Urban attractions were conventionally identified by Alhazzani [19] via the notion of road network sites of interest. This study additionally identified attraction patterns by analyzing visitor numbers, visitor distance distribution, and visitor origin spatial dispersion.…”
Section: Research Statusmentioning
confidence: 99%